Determination of metals in natural waters, sediments and soils - Crompton, T. R. (Thomas Roy) (Elsevier, 2015)
Determination of Metals in Natural Waters, Sediments and Soils provides analytic labs with a comprehensive overview of the various methods available for analysis of metals and serves as a manual to determine metal concentrations in different media such as natural waters, waste waters, sediments and soils. The book begins with a discussion of sampling techniques and preservation and then covers metals in rivers, surface ground and mineral waters and metals in aqueous precipitation. It concludes with detailed information on analysis of metals in sediments. Determination of Metals in Natural Waters, Sediments and Soils provides a foundation for informed action by environmental interest groups and regulators and a starting point for further study by graduate students, professionals, and researchers.--Provided by publisher.